2014
DOI: 10.1111/edt.12108
|View full text |Cite
|
Sign up to set email alerts
|

The direct cytotoxic effects of medicaments used in endodontic regeneration on human dental pulp cells

Abstract: The low concentrations of intracanal medicaments tested in this study were not cytotoxic in cultured cells. However, these concentrations are much lower than the concentrations that have been advocated in endodontic regeneration. Furthermore, the negative effects of TAP on DPCs were detected at lower concentrations by using the WST-1 assays than by measuring the LDH release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 25 publications
(37 reference statements)
5
54
1
1
Order By: Relevance
“…A recent study reported that 0.3-2.5 mg/mL of TAP and 0.5-1 mg/mL of DAP were not toxic to dental pulp fibroblasts using LDH assays [15]. The difference in detected cytotoxic concentrations using LDH assays between the current and previous study could be explained by the different type of cells used (pulp stem cells versus pulp fibroblasts).…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…A recent study reported that 0.3-2.5 mg/mL of TAP and 0.5-1 mg/mL of DAP were not toxic to dental pulp fibroblasts using LDH assays [15]. The difference in detected cytotoxic concentrations using LDH assays between the current and previous study could be explained by the different type of cells used (pulp stem cells versus pulp fibroblasts).…”
Section: Discussioncontrasting
confidence: 52%
“…This could be explained by the capability of the WST-1 to detect change in mitochondrial metabolic activities inside the cells that may precede the cell membrane destruction detected by LDH assays. Previous studies that used pulp fibroblasts or other types of cells have also reported earlier 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 detection of cytotoxicty using WST-1 assays compared to LDH assays [15,33,34]. Various cytotoxic assays may give different cytotoxic results depending on the measured physiological endpoint.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations